Gametophyte niche differences among sympatric tree ferns. (16th January 2019) - Brock, James M. R.; Burns, Bruce R.; Perry, George L. W.; Lee, William G.
Abstract : Forest community assembly is usually framed in terms of sporophyte dynamics; however, the recruitment and maintenance of fern populations, frequently influential in forest composition and structure, are initially determined by gametophytes. Sporophytes of three Cyathea tree fern species show habitat partitioning along gradients of phosphorus and light; we asked whether gametophyte niche differences parallel this pattern. To compare niche characteristics among taxa we compared growth rates to a size threshold (≥3 mm) of gametophytes under controlled conditions using a multi-factorial, multi-level (3 × 4) experiment, varying irradiance (5.4 ± 4.4; 59.1 ± 44.3; 107 ± 74.1 µmol m −2 s −1 ) and orthophosphate concentrations (5, 10, 20, 40 mg kg −1 ). Gametophytes of the pioneer species C. medullaris developed to the size threshold across a broad range of phosphate and irradiance treatments (more than 20% of gametophytes in ≥ 7 of the 12 treatments), peaking at 20 mg kg −1 P and 60 µmol m −2 s −1 irradiance. The growth rates of the forest understorey species C. dealbata and C. smithii also peaked at 60 µmol m −2 s −1 but varied across treatments, suggesting niche differentiation along irradiance and orthophosphate gradients. Our analysis suggests that gametophyte development is strategically aligned to the ecological habits of sporophytes and that forest community assembly is likely strongly influenced by the independent gametophyte life-stage.